Mycobacterium microti: Not Just a Coincidental Pathogen for Cats - Peterhans, Sophie; Landolt, Patricia; Friedel, Ute; Oberhänsli, Francisca; Dennler, Matthias; Willi, Barbara; Senn, Mirjam; Hinden, Sandro; Kull, Karin; Kipar, Anja; Stephan, Roger; Ghielmetti, Giovanni (Frontiers in Veterinary Science, 2020)
Public interest in animal tuberculosis is mainly focused on prevention and eradication of bovine tuberculosis in cattle and wildlife. In cattle, immunodiagnostic tests such as the tuberculin skin test or the interferon gamma (IFN-γ) assay have been established and are commercially available. Feline tuberculosis is rather unknown, and the available diagnostic tools are limited. However, infections with Mycobacterium tuberculosis complex members need to be considered an aetiological differential diagnosis in cats with granulomatous lymphadenopathy or skin nodules and, due to the zoonotic potential, a time-efficient and accurate diagnostic approach is required. The present study describes eleven independent cases of Mycobacterium microti infection in domestic cats in Switzerland. For three cases, clinical presentation, diagnostic imaging, bacteriological results, immunodiagnostic testing and pathological features are reported. An adapted feline IFN-γ release assay was successfully applied in two cases and appears to be a promising tool for the ante mortem diagnosis of tuberculosis in cats. Direct contact with M. microti reservoir hosts was suspected to be the origin of infection in all three cases. However, there was no evidence of M. microti infection in 346 trapped wild mice from a presumptive endemic region. Therefore, the source and modalities of infection in cats in Switzerland remain to be further elucidated.